Mycoplasma Genitalium Among Women With Nongonococcal, Nonchlamydial Pelvic Inflammatory Disease - Catherine L. Haggerty; Patricia A. Totten; Sabina G. Astete; Roberta B. Ness (Hindawi Limited, 2006)
Pelvic inflammatory disease (PID) is a frequent condition of young women, often resulting in reproductive morbidity. Although Neisseria gonorrhoeae and/or Chlamydia trachomatis are/is recovered from approximately a third to a half of women with PID, the etiologic agent is often unidentified. We need PCR to test for M genitalium among a pilot sample of 50 women with nongonococcal, nonchlamydial endometritis enrolled in the PID evaluation and clinical health (PEACH) study. All participants had pelvic pain, pelvic organ tenderness, and leukorrhea, mucopurulent cervicitis, or untreated cervicitis. Endometritis was defined as ≥5 surface epithelium neutrophils per ×400 field absent of menstrual endometrium and/or ≥2 stromal plasma cells per ×120 field. We detected M genitalium in 7 (14%) of the women tested: 6 (12%) in cervical specimens and 4 (8%) in endometrial specimens. We conclude that M genitalium is prevalent in the endometrium of women with nongonococcal, nonchlamydial PID.